A SURVEY OF DEATH ADJUSTMENT IN THE INDIAN SUBCONTINENT - Hossain, Mohammad Samir; Irfan, Muhammad; Balhara, Yatan Pal Singh; Giasuddin, Noor Ahmed; Sultana, Syeda Naheed (Journal of Ayub Medical College Abbottabad, 2015)
Background: The Death Adjustment Hypothesis (DAH) postulates two key themes. Its first part postulates that death should not be considered the end of existence and the second part emphasizes that the belief in immortal pattern of human existence can only be adopted in a morally rich life with the attitude towards morality and materialism balanced mutually. We wanted to explore Death Adjustment in the Indian subcontinent and the differences among, Indians, Pakistanis and Bangladeshis. We also wanted to find the relationship between death adjustment (i.e., adaptation to death), materialistic thoughts and death adjustment thoughts. Methods: This was a cross-sectional study, conducted from May 2010 to June 2013. Using a purposive sampling strategy, a sample of 296 participants from the Indian subcontinent [Pakistan (n=100), Bangladesh (n=98) and India (n=98)] was selected. Multidimensional Fear of Death Scale (MFODS) was used to measure death adjustment. The rest of the variables were measured using lists of respective thoughts, described in elaborated DAH. Analyses were carried out using SPSSv13. Results: The mean death adjustment score for Pakistani, Indian and Bangaldeshi population were 115.26±26.4, 125.87±24.3 and 114.91±21.2, respectively. Death adjustment was better with older age (r=0.20) and with lower scores on materialistic thoughts (r=-0.26). However, this was a weak relation. The three nationalities were compared with each other by using Analysis of variance. Death adjustment thoughts and death adjustment were significantly different when Indians were compared with Bangladeshis (p=0.00) and Pakistanis (p=0.006) but comparison between Bangladeshis and Pakistanis showed no significant difference. Conclusions: Subjects with lesser materialistic thoughts showed better death adjustment. There are differences between Muslims and non-Muslims in adjusting to death. Keywords: Death Adjustment Hypotheses (DAH), Death adjustment, Materialism, Existence, Afterlife